Epoka University, Master of Science in Banking and Finance - Shima, Jetnor (Richtmann Publishing, 2012)
This paper examines inflation and nominal exchange rate in Albania during this economical transition period including 1995-1996 until 2010-2011 for Albanian economic system. Several channels through which inflation can affect wellness of Albanian citizenand investigate the relationship on variables of the economy. Beginning from a low base years1996-97, Albania has quickly reached tohigh GDP growth and decreasing inflation, in conjunction with serious efforts thought open-market reforms.So the aim is to investigatethe impact of consumer price change on exchange rate. How much does the inflation effect on the exchange rate, also we will discuss ifinflation has a significant positive or negative impact of exchange stability on real growth and it will analyze costs and benefits ofexchange rate stabilization in Albania during these 15 years. In this paper, an important role plays the effect of the exchange rate regimeon economic growth. As a whole, this literature is inconclusive mainly because there are theoretical channels highlighting a positiveeffect of exchange rate stability on growth and others that stress the negative repercussions of exchange rate that has on outputexpansion. The paper concludes that the inflation in Albania does not have much effect on nominal exchange rate and in other part theassociation of exchange rate stability with higher real growth remains lusty. Exchange rate has different dependent variable in Albania.This result will be proved and estimated a linear regression model key of macroeconomic variables.